Minimally Invasive Myomectomy: Practice Trends and Differences Between Black and Non-Black Women Within a Large Integrated Healthcare System. Issue 9 (September 2022) - Zaritsky, Eve; Le, Amy; Tucker, Lue-Yen; Ojo, Anthonia; Weintraub, Miranda Ritterman; Raine-Bennett, Tina
Abstract : (Abstracted from Am J Obstet Gynecol 2022;226:826.e1–826.e11) Some studies indicate that up to 80% of Black women will develop uterine fibroids. Hysterectomy, the definitive surgical option for women with symptomatic fibroids, is not an option for those who have not completed childbearing or wish to preserve their fertility.